Lycopene protects against cyclosporine A-induced testicular toxicity in rats - Türk, G; Ateşşahin, A; Sönmez, M; Yüce, A; Çeribaşı, Ao (My University, 2007)
Cyclosporine A (CsA)-induced direct failures in hypothalamic–pituitary–gonadal axis and Sertoli cell phagocytic function have been considered for testicular toxicity so far. It has clearly been reported that oxidative stress leads to damage in sperm functions and structure of the testis. Therefore, this study was conducted to demonstrate whether CsA causes testicular and spermatozoal toxicity associated with the oxidative stress, and to investigate the possible protective effect of lycopene against CsA-induced damages in all reproductive organs and sperm characteristics in male rats. While the daily administration of CsA at the dose 15 mg/kg for 21 days significantly decreased the seminal vesicles weight, epididymal sperm concentration, motility, testicular tissue glutathione (GSH), glutathione peroxidase (GSH-Px) and catalase (CAT), diameter of seminiferous tubules and germinal cell thickness, it increased malondialdehyde (MDA) level and abnormal sperm rates along with degeneration, necrosis, desquamative germ cells in testicular tissue. However, the CsA along with simultaneous administration of lycopene at the dose of 10 mg/kg markedly ameliorated the CsA-induced all the negative changes observed in the testicular tissue, sperm parameters and oxidant/antioxidant balance. In conclusion, CsA-induced oxidative stress leads to the structural and functional damages in the testicular tissue and sperm quality of rats and, lycopene has a potential protective effect on these damages.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Cyclosporine A Lycopene Oxidative stress Reproductive organs Sperm characteristics